Validation and Reliability of Indonesian Version of Vitiligo-Specific Health-Related Quality of Life Instrument (VITIQoL) - Indramaya, Diah Mira; Devi, Aprilin Krista; Sawitri; Utomo, Budi; Fithriyah, Izzatul; Murtiastutik, Dwi; Hidayati, Afif Nurul; Cita Rosita Sigit Prakoeswa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: Vitiligo is a long-term autoimmune disorder marked by the loss of melanocytes and the formation of white macules. Vitiligo can have an impact on the patient's look and quality of life. The Dermatology Life Quality Index (DLQI) is a questionnaire that analyzes the quality of life of skin patients in general, but it is not disease-specific. To assess the quality of life of vitiligo patients in Indonesia, a disease-specific instrument is required. Purpose: This study aims to analyze the validity and reliability of the Vitiligo Quality of Life (VitiQol) questionnaire in Indonesia and translate the VitiQol questionnaire into Indonesian. Methods: Using cross-sectional analytic observation, this study was performed on 39 participants with vitiligo at Dr. Soetomo Surabaya between December 2021 and January 2022. The investigation consisted of three phases: the Indonesian translation of VitiQol, testing for validity, and assessing reliability. Result: The VitiQol questionnaire is a valid and reliable questionnaire. Valid with a correlation coefficient between 0.40 and 0.80 and reliability close to perfection. There was a significant correlation between VitiQol and DLQI (r=0.511, p=0.001). Conclusion: According to the findings of this study, the Indonesian VitiQol is a valid and reliable instrument for measuring the life quality of vitiligo patients in Indonesia.